INTEGRATED MANAGEMENT IN FOOD AND NUTRITION UNITS (UAN): THE ROLE OF THE NUTRITIONIST IN DAILY OPERATIONS, FROM HUMAN RESOURCES TO PHYSICAL STRUCTURE (Editora Impacto Científico, 2024)
This study analyzed the importance of integrated management in Food and Nutrition Units (FNUs), focusing on the interconnection between Human Resources, physical structure, menu planning, and food safety. Daily management is crucial as the sector faces significant challenges. Human capital is vulnerable due to the low qualification of food handlers, which directly impacts the correct application of Good Practices (BPM). Deficiencies frequently observed in the physical structure, such as the lack of temperature control equipment and inadequate layout, compromise sanitary safety. Furthermore, menu planning must be rigorous to mitigate nutritional risk (such as excessive fat in preparations) and promote sustainability through effective waste generation control. It is concluded that the Nutritionist is the irreplaceable leader and technical manager in the FNU, whose role is essential for integrating Dietetic Technique, legislation, and people management, ensuring operational excellence, comensal safety, and service sustainability.DOI: https://doi.org/10.56238/edimpacto2025.090-034